Pretreatment advanced lung cancer inflammation index (ALI) for predicting early progression in nivolumab‐treated patients with advanced non–small cell lung cancer. (18th November 2017) - Shiroyama, Takayuki; Suzuki, Hidekazu; Tamiya, Motohiro; Tamiya, Akihiro; Tanaka, Ayako; Okamoto, Norio; Nakahama, Kenji; Taniguchi, Yoshihiko; Isa, Shun‐ichi; Inoue, Takako; Imamura, Fumio; Atagi, Shinji; et al.
Abstract: Programmed death‐ligand 1 (PD‐L1) expression status is inadequate for indicating nivolumab in patients with non–small cell lung cancer (NSCLC). Because the baseline advanced lung cancer inflammation index (ALI) is reportedly associated with patient outcomes, we investigated whether the pretreatment ALI is prognostic in NSCLC patients treated with nivolumab. We retrospectively reviewed the medical records of all patients treated with nivolumab for advanced NSCLC between December 2015 and May 2016 at three Japanese institutes. Multivariate logistic regression and Cox proportional hazards models were used to assess the impact of the pretreatment ALI (and other inflammation‐related parameters) on progression‐free survival (PFS) and early progression (i.e., within 8 weeks after starting nivolumab). A total of 201 patients were analyzed; their median age was 68 years (range, 27–87 years), 67% were men, and 24% had an Eastern Cooperative Oncology Group (ECOG) performance status of 2 or higher. An ECOG performance status ≥2, serum albumin <3.7 g/dL, neutrophil‐to‐lymphocyte ratio ≥4, and ALI <18 were significantly associated with poor PFS and early progression on univariate analysis. Multivariate analyses revealed that pretreatment ALI <18 was independently associated with inferior PFS (median, 1.4 vs. 3.7 months, P < 0.001) and a higher likelihood of early progression (odds ratio, 2.76; 95% confidence interval 1.44–5.34; P = 0.002). The pretreatment ALI was found to be a significant independent predictor of early progression in patients with advanced NSCLC receiving nivolumab, and may help identify patients likely to benefit from continued nivolumab treatment in routine clinical practice. Abstract : Pretreatment ALI was a significant independent predictor of early progression in advanced NSCLC patients receiving nivolumab. This may be useful for clinical decision making by identifying patients who may benefit from continued nivolumab treatment.